UMP sends volunteers to focus on clean-up operations and aid distribution - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
MENTAKAB, 27 December 2021 - Focusing on clean-up operations and aid distribution, 100 Universiti Malaysia Pahang (UMP) volunteers spent two days to help clean up students’ houses and neighbourhoods in Taman Mentakab Indah which were badly affected by the recent floods.